Inventarisasi Jenis-Jenis Ikan di Kawasan Ekowisata Hutan Bakau Kuala Langsa, Kota Langsa, Aceh - Hijratul Abdi; Cut Nanda Defira; Zuriana Siregar; Irvianty Irvianty; Suwarno Suwarno; Aida Fithri (Universitas Syiah Kuala, 2025)
The Kuala Langsa Mangrove Forest Area is a mangrove ecosystem in Langsa City that has been designated as an ecotourism area. The conversion of the Kuala Langsa mangrove forest area into an ecotourism area is suspected to cause changes in fish habitat, thus affecting fish populations. Research on fish species inventory in the mangrove forest ecotourism area is very relevant to understand the negative impacts of ecotourism on fish and the surrounding environment. An inventory of fish species in the Kuala Langsa Mangrove Forest Ecotourism Area was conducted from February to August 2024. This study aims to determine the species of fish found in the Kuala Langsa Mangrove Forest Ecotourism Area. The method used was an exploratory survey, by exploring the Kuala Langsa Mangrove Forest Ecotourism Area. The search started from the observation tower area to the river mouth. Sampling points were adjusted to environmental conditions, namely depth and habitat conditions. Sample collection was carried out using gill nets and nets, with 9 gill net installation points and 18 net throwing points. Sampling was carried out three times at each location. The research results obtained 90 individuals, consisting of 16 families and 18 species. The species with the largest number of individuals was found in the Gerres erythrourus (kapas) species with 12 individuals, followed by the Hyporhamphus balinensis (julung) species with 11 individuals, and the Sillago sihama (rejung) species with 9 individuals. The least number of species was found in the Caranx ignobilis (rambeu), Platycephalus indicus (baji-baji) and Lactoria cornuta (helicopter) species with one individual each.